Molecular Survey on Toxoplasma gondii and Neospora caninum Infection in Wild Birds of Prey Admitted to Recovery Centers in Northern Italy - Alessia Libera Gazzonis; Luca Villa; Emanuele Lubian; Sara Ressegotti; Guido Grilli; Stefano Raimondi; Sergio Aurelio Zanzani; Maria Teresa Manfredi (Microorganisms, 2021)
Toxoplasma gondii and Neospora caninum (Apicomplexa, Sarcocystidae) are protozoan parasites infecting a wide range of intermediate hosts worldwide, including birds. Raptors acquire the infections through the ingestion of both infected preys and oocysts in the environment suggesting they might be used as indicators of the spread of these pathogens. Here, we report an epidemiological survey with the aim of determining the prevalence of T. gondii and N. caninum infections in wild birds of prey, hospitalized in two Wildlife Recovery Centres (WRCs) in Northern Italy. Genomic DNA extracted from brain tissue samples was submitted to Real Time PCR targeting T. gondii B1 and N. caninum Nc5 genes. T. gondii genotyping was then performed by multilocus sequence typing (MLST) analysis, targeting three polymorphic genes (GRA6, BTUB, and altSAG2). T. gondii DNA was found in 35 (62.5%) out of 56 examined samples; concerning genotyping, it was possible to amplify at least one gene for 26 animals, and obtained sequences belonged to Type II. N. caninum DNA was only detected in two (3.6%) common kestrels (Falco tinnunculus), adding a new species to the list of suitable intermediate hosts for this pathogen. Data obtained in the present study thus confirmed the spread of both T. gondiiand N. caninum in wild bird of prey, endorsing the role of WRCs in the epidemiological surveillance of wildlife.